Efficacy of Intravenous Versus Oral Administration of Levocarnitine in Maintenance Hemodialysis Patients: A Randomized Controlled Trial Investigating Therapeutic Approaches to Renal Anemia - Sadia Rehman; Muhammad Farhan; Santosh Kumar; Muhammad Raza Sarfraz; Asma Naveed; Muhammad Tassaduq Khan; Hiya Huq (Health Science Reports)
ABSTRACT Background and Aim Carnitine deficiency contributes to various comorbidities in maintenance hemodialysis (MHD) patients. This study aims to assess the impact of levocarnitine supplementation on hematological and serum iron profile parameters, comparing the efficacy of oral versus intravenous (IV) administration in these patients. Materials and Methods This was a multicenter, randomized controlled trial was conducted on patients undergoing MHD at the hemodialysis unit of our study center in Karachi, Pakistan. Eligible patients were randomly assigned to either the oral or IV groups. Patients in the oral group received levocarnitine tablets of 500 mg three times daily, while patients in the IV group received an IV bolus of levocarnitine at a dose of 20 mg/kg body weight, infused over 2–3 min directly into the IV line after each hemodialysis session. Both groups received intervention for a total of 24 weeks, and the final analysis included 49 patients from the oral group and 34 patients from the IV group. Results The study involved 83 patients with a mean age of 44.72 ± 8.77 years, with a balanced distribution of 41 males and 42 females. The IV group showed a significant improvement in hemoglobin levels (mean increase: 0.57 g/dL, p < 0.001) and hematocrit (mean increase: 3.83%, p = 0.001), while the oral group showed only slight, nonsignificant changes in hemoglobin (mean increase: 0.07 g/dL, p = 0.22). Serum iron profile parameters improved significantly in both groups, though the IV group demonstrated greater enhancements across all parameters. Hematological parameter analysis revealed significant post‐intervention differences in hemoglobin, MCH, and MCHC, favoring the IV group. Conclusion levocarnitine improves the hematological and iron profile in MHD patients. However, IV levocarnitine significantly more effective than oral administration. It notably improves hemoglobin, and enhances iron profile parameters. Trial Registration ClinicalTrials.gov: NCT05817799.